Rain attenuation predictions on terrestrial radio links: differential equations approach - Abdulrahman, A Y; Rahman, T A; Rahim, S K A; Islam, Md Rafiqul; Abdulrahman, M K A (John Wiley, 2012)
The results of rain attenuation on terrestrial microwave links in a tropical climate has been reported in this paper. The results are presented in the form of rate of change of attenuation with respect to rain rate, denoted by S.R%p/. This is in turn used for predicting the expected rain attenuation at any %p of the time rain rate is exceeded in any tropical location. The predictions of the proposed model have been validated using the data collected in six locations in Malaysia and experimental results reported in other tropical locations that have a similar rainfall regime. The Malaysian data consist of 1-year measured rain attenuation over six DIGI MINI-LINKs operating at 15 GHz, and rainfall rates measured with both 1-minute and 1-hour integration times at the respective locations. The validity of the proposed model is further validated by comparing its estimates with the method of ITU-R Radiocommunication Sector of ITU and two classical rain attenuation prediction models particularly developed for tropical regions.The test results have shown that the proposed method seems to be more accurate than the proposed method seems to be more accurate than ITU-R and the other two prediction models in Malaysia. The method could be used as an alternative approach for predicting rain attenuation over any terrestrial microwave links in Malaysia and similar tropical climates. Copyright © 2012 John Wiley & Sons, Ltd.